User-Centered Design in the AIRAF Interface: Reducing Cognitive Load and Supporting Self-Regulated Learning - Nissa Arrumaisha; Rizki Hikmawan; Dinda Alya Maghfira; Rochman Bambang Eko Saputro (Universitas Pendidikan Mandalika, 2026)
This study aims to evaluate the usability, user experience, and cognitive load of the AIRAF interface using a User-Centered Design (UCD) approach through two iterative evaluation phases. In the first evaluation phase (UE1), eight undergraduate students completed a series of structured interaction tasks using Maze and subsequently responded to the System Usability Scale (SUS), User Experience Questionnaire (UEQ), and External Cognitive Load (ECL) questionnaire. The data were analyzed descriptively by calculating task performance indicators, mean questionnaire scores, and comparative changes between UE1 and UE2. The results of UE1 showed a marginal SUS score of 62, a UEQ mean score of 1.45, and an ECL mean score of 7.28, indicating usability issues related to typography, navigation, visual clarity, and feature recognition. Following the interface redesign, a second evaluation phase (UE2) involving ten participants demonstrated substantial improvements. The SUS score increased to 80, the UEQ mean score improved to 1.97, and the ECL mean score increased to 8.75, with improvements observed across all UEQ dimensions. These findings suggest that the UCD approach effectively simplifies complex AI-supported learning interfaces by enhancing visual hierarchy, interaction clarity, and feedback presentation, thereby reducing students' confusion and unnecessary cognitive effort during interaction.